A prospective observational study on the feasibility of subumbilical laparoscopic procedures under epidural anesthesia in sedated spontaneously breathing infants with a natural airway. Issue 1 (8th October 2021) - Opfermann, Philipp; Marhofer, Peter; Springer, Alexander; Metzelder, Martin; Zadrazil, Markus; Schmid, Werner
Abstract: Background: Laparoscopic procedures are usually performed under general anesthesia with a secured airway including endotracheal intubation or supraglottic airways. Aims: This is a prospective study of the feasibility of subumbilical laparoscopic procedures under epidural anesthesia in sedated, spontaneous breathing infants with a natural airway. Methods: We consecutively enrolled 20 children <3 years old with nonpalpable testes scheduled for diagnostic laparoscopy with or without an ensuing orchidopexy, inguinal revision, or Fowler‐Stephens maneuver. Inhalational induction for venous access was followed by sedation with propofol and ultrasound‐guided single‐shot epidural anesthesia via the caudal or thoracolumbar approach using 1.0 or 0.5 ml kg −1 ropivacaine 0.38%, respectively. The primary outcome measure was block success, defined as no increase in heart rate by >15% or other indicators of pain upon skin incision. Results: Of the 20 children (median age: 10 months; IQR: 8.3−12), 17 (85%) were anesthetized through a caudal and 3 (15%) through a direct thoracolumbar epidural, 18 (90%) underwent a surgical procedure and 2 (10%) diagnostic laparoscopy only. Five patients (25%) received block augmentation using an intravenous bolus of fentanyl (median dose: 0.9 µg kg −1 ; IQR: 0.8−0.95) after the initial prick test and before skin incision. There was no additional need for systemic pain therapy in the operating theater or recovery room. No events of respiratory failure or aspiration were observed. Conclusions: In experienced hands, given our success rate of 100%, epidural anesthesia performed in sedated spontaneously breathing infants with a natural airway can be an alternative strategy for subumbilical laparoscopic procedures.